Preliminary analysis of the aluminium-timber composite beams = Analiza wstępna belek zespolonych aluminiowo-drewnianych - Szumigała, Maciej; Chybiński, Marcin; Polus, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents a new type of composite structures - aluminium-timber beams. These structures have an advantage over other existing composite structures, because they are lighter. However, their application may be limited due to the high price of aluminium alloys. The authors of this article made an attempt to calculate the load-bearing capacity of an aluminium-timber beam.
Keywords: composite structures; constructions aluminium-timber; composite beams; FEM; ABAQUS; konstrukcje kompozytowe; konstrukcja aluminiowo-drewniana; belka zespolona; MES